2015
DOI: 10.1021/tx5004886
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of DNA Adducts and Corresponding Tissue Damage of Sprague–Dawley Rats with Percutaneous Exposure to Sulfur Mustard

Abstract: Sulfur mustard (SM) is a highly reactive alkylation vesicant and cytotoxic agent that has been recognized as an animal and human carcinogen. Although the exact mechanism of toxicology is vague, DNA alkylation seems to be responsible for the triggering of apoptosis. In this study, after male adult Sprague-Dawley rats were cutaneous exposed to a low concentration of SM at parts-per-million levels, their lungs, livers, pancreases, spleens, marrow, and brains were collected at 11 different time points and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
4
27
2
Order By: Relevance
“…By comparison, our previous work reported that the maximum level of N 7 -HETEG in the liver from a 10 mg/kg dose exposed rat was approximately 98 ± 62 per 10 6 bases. 25 There were multiple magnitude differences between the adduct levels in the ATs and other tissues. These results were different from the comparative results in vitro and may be a result of a more complex physiological environment in vivo.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, our previous work reported that the maximum level of N 7 -HETEG in the liver from a 10 mg/kg dose exposed rat was approximately 98 ± 62 per 10 6 bases. 25 There were multiple magnitude differences between the adduct levels in the ATs and other tissues. These results were different from the comparative results in vitro and may be a result of a more complex physiological environment in vivo.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
“…25 SM has lipophilic properties. 26 It has been suggested that the accumulation of SM in adipose or hydrophobic environments (such as lipids) and the subsequent biological effects may be crucial for the distribution of and damage caused by SM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Depletion of white blood cells is a well reported facet of SM toxicity, and it has been suggested that the SM-mediated immune suppression may be one of the most threatening effects of exposure (Anderson et al, 2006;Hassan et al, 2006;Yue et al, 2015). These studies also found SM exposure to produce a leukopenia that was primarily influenced by depressed lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytic antioxidant administration attenuated leukopenia at each time point studied with the largest effects on the neutrophil and lymphocyte counts. The finding that white blood cells are restored with catalytic antioxidant treatments is highly significant due to the previous research which has shown bone marrow to be an important target of SM damage (Yue et al, 2015). Leukocytes are believed to have an important role in the pathogenic response to inhaled vesicants (McClintock et al, 2002;Weinberger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These ions are potent alkylating molecules that react with nucleotides, proteins, and lipids. Because of its strong alkylating properties, primarily due to activity at guanine residues, SM forms DNA adducts and cross‐links . SM is partially absorbed from the skin into the dermis, where it can form DNA adducts or enter systemically and react with other organs, including the lung .…”
Section: Sulfur Mustard Toxicitymentioning
confidence: 99%